The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s11205-023-03140-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the COVID-19-induced Lockdown on the Social Capital and Cultural Capital in Italy

Abstract: The present study investigated the effects of the first COVID-19 lockdown on the Cultural and Social Capitals in Italy in a large group of adults (n = 1125). The relationships between the COVID-19 spread and participants’ Cultural Capital, Social Capital, educational level, occupational prestige, and age were studied using structural equation models. For women but not for men, pandemic spread was positively affected by occupational prestige and it had a positive relationship with their Social Capital (women: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Similarly, increase of activeness was observed in more villages in the second year than in the first one. In community centres and rural women's clubs the decrease was much more visible in those organisations that were initially active, which contradicts the observations done by Menardo et al (2023). Perhaps this is because they nowadays play rather a role of socialising than of typical NGOs.…”
Section: Changes In Social Activeness Due To Pandemicmentioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, increase of activeness was observed in more villages in the second year than in the first one. In community centres and rural women's clubs the decrease was much more visible in those organisations that were initially active, which contradicts the observations done by Menardo et al (2023). Perhaps this is because they nowadays play rather a role of socialising than of typical NGOs.…”
Section: Changes In Social Activeness Due To Pandemicmentioning
confidence: 75%
“…Thus there is no clear trend visible in the data. Research carried out in Italy between March and May 2020 revealed that after the outspread of pandemic people with higher social capital became more active, while whose with lower level of social capital became less active (Menardo et al 2023). To check this phenomenon in Polish conditions, a comparison of active and inactive organisations was carried out (Table 1.…”
Section: Changes In Social Activeness Due To Pandemicmentioning
confidence: 99%